Strategic management : formulation, implementation, and control - Pearce, John A.; Robinson, Richard B. (Boston : Irwin/McGraw-Hill, 2000)
Focusing on strategic management, this text presents contemporary research in the area and emphasizes conceptual tools and skills. It contains multiple "Business Week" and traditional strategic management cases, and presents a pedagogical model created by the authors.
Includes bibliographical references and indexes.
oif 12/03/15
Loan
Keywords: Strategic planning; Strategic Management